Commotio Cordis - Madias, Christopher (Indian Heart Rhythm Society, 2007)
Sudden arrhythmic death as a result of a blunt chest wall blow has been termed Commotio Cordis (CC). CC is being reported with increasing frequency with more than 180 cases now described in the United States Commotio Cordis Registry. The clinical spectrum is diverse; however young athletes tend to be most at risk, with victims commonly being struck by projectiles regarded as standard implements of the sport. Sudden death is instantaneous and victims are most often found in ventricular fibrillation (VF). Chest blows are not of sufficient magnitude to cause any significant damage to overlying thoracic structures and autopsy is notable for the absence of any structural cardiac injury. Development of an experimental model has allowed for substantial insights into the underlying mechanisms of sudden death. In anesthetized juvenile swine, induction of VF is instantaneous following chest impacts that occur during a vulnerable window before the T wave peak. Other critical variables, including the impact velocity and location, and the hardness of the impact object have also been identified. Rapid left ventricular pressure rise following chest impact likely results in activation of ion channels via mechano-electric coupling. The generation of inward current through mechano-sensitive ion channels results in augmentation of repolarization and non-uniform myocardial activation, and is the cause of premature ventricular depolarizations that are triggers of VF in CC. Currently available chest protectors commonly used in sport are not adequately designed to prevent CC. The development of more effective chest protectors and the widespread availability of automated external defibrillators at youth sporting events could improve the safety of young athletes.